The Effect of Various Types of Ameliorants on the Growth, Yield, and Quality of Mendong (Fimbristylis globulosa) - Hidayat, Egi Agus Nur; Amanda, Adinda Putri; Rosmala, Arrin (Jurnal Biologi Tropis, 2025)
Mendong (Fimbristylis globulosa) is a fiber-producing plant with high economic value, widely utilized in traditional handicraft industries. However, declining land quality has reduced its productivity, necessitating soil improvement through ameliorant application to enhance its growth and product quality. This study aims to examine the effects of various ameliorant types on the growth, yield, and quality of mendong. The research employed a Randomized Block Design (RBD) with four treatments: no ameliorant (control/P0), goat manure (P1), dolomite (P2), and rice husk charcoal (P3). Each treatment was repeated six times, resulting in 16 experimental units with four plant samples per unit. Observed parameters included plant height, number of tillers, number of flowers, fresh and dry biomass, fresh and dry root weight, root length, and percentage of marketable clumps. Data were analyzed using ANOVA followed by LSD at a 5% significance level. The results showed that ameliorant application did not significantly affect plant height, number of flowers, fresh and dry biomass, root weight, nor root length. However, a significant effect was observed on the number of tillers at 5, 9, and 12 WAP, as well as on the percentage of marketable clumps. Goat manure (P1) generally produced the best performance in most parameters, particularly in product quality, with marketable clumps reaching 75%, higher than other treatments. These findings indicate that goat manure is the most effective ameliorant for improving mendong product quality.